2012
DOI: 10.1093/hmg/dds489
|View full text |Cite
|
Sign up to set email alerts
|

Common variation at 2q22.3 (ZEB2) influences the risk of renal cancer

Abstract: Genome-wide association studies (GWASs) of renal cell cancer (RCC) have identified four susceptibility loci thus far. To identify an additional RCC common susceptibility locus, we conducted a GWAS and performed a meta-analysis with published GWASs (totalling 2215 cases and 8566 controls of European background) and followed up the most significant association signals [nine single nucleotide polymorphisms (SNPs) in eight genomic regions] in 3739 cases and 8786 controls. A combined analysis identified a novel sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 25 publications
(35 reference statements)
1
43
0
1
Order By: Relevance
“…Logistic regression is used throughout to test for association between SNPs and disease. Results for the fifth variant, located on 2q22.3, are nonsignificant but the effect is in the same direction as originally reported 7 (P ¼ 0.51, odds ratio (OR) ¼ 1.10).…”
Section: Gwas Data and Imputation In Icelandic Samplessupporting
confidence: 78%
See 1 more Smart Citation
“…Logistic regression is used throughout to test for association between SNPs and disease. Results for the fifth variant, located on 2q22.3, are nonsignificant but the effect is in the same direction as originally reported 7 (P ¼ 0.51, odds ratio (OR) ¼ 1.10).…”
Section: Gwas Data and Imputation In Icelandic Samplessupporting
confidence: 78%
“…Rare, high-penetrance mutations accounting for syndromic RCC have been found in several genes, including VHL, MET, FLCN and FH 4 . Genome-wide association studies (GWAS) have reported five sporadic RCC susceptibility loci [5][6][7] . However, in combination, these risk variants account for only a small fraction of the approximately twofold greater than the average risk of RCC in first-degree relatives of RCC patients 1,2 .…”
mentioning
confidence: 99%
“…The SNP is located in an enhancer regulatory feature (Rosenbloom et al 2011;Dunham et al 2012) located between genes PELI1 and VPS54, in the same putatively selected region as that of genes EHBP1 and OTX1 (see above). Finally, there is a highly C-scoring SNP (rs731108) that is associated with renal cell carcinoma (Henrion et al 2013). This SNP is also located in an enhancer regulatory feature (Rosenbloom et al 2011;Dunham et al 2012), in an intron of ZEB2.…”
Section: Selection In Ancestral Modern Humansmentioning
confidence: 99%
“…Recent genome-wide association studies (GWAS) conducted among study populations of European ancestry have identified four susceptibility loci for RCC (68). The variant rs7579899 maps to EPAS1 on 2p21, which encodes HIF-2α, a critical factor in HIF/VHL-mediated development of ccRCC (5).…”
Section: Introductionmentioning
confidence: 99%
“…The variant rs7579899 maps to EPAS1 on 2p21, which encodes HIF-2α, a critical factor in HIF/VHL-mediated development of ccRCC (5). The variants rs7105934, on 11q13.3, and rs12105918, mapping to ZEB2 on 2q22.3, are also suspected to influence RCC risk in a HIF-dependent manner (6, 8, 9). The biologic basis for the association with rs718314 (mapping to ITPR2 on 12p11.23) is unclear, although ITPR2 was associated with waist-to-hip ratio in an earlier GWAS (10); the latter is interesting because an elevated BMI is an established risk factor for RCC in all populations studied (2).…”
Section: Introductionmentioning
confidence: 99%